Applications Learning Musical Instruments in Indonesia Using Augmented Reality Technology - Rahmawati Febrifyaning Tias (Fakultas Teknik Universitas Bhayangkara, 2020)
The 3-dimensional animation designed and presented as learning media has grown rapidly nowadays, 3-dimensional animated characters in regional musical instruments can be one of the learning media for the general public especially children. How to present different learning 3-dimensional animation content, can attract the general public and children to learn, one of them using augmented reality technology. Augmented reality is the practice of combining image media with a 3-dimensional object that brings out 3- dimensional objects from cyberspace to the real world. This way can be a form of learning, where users can see and understand that learning can be conveyed through efficient learning, in the concept of augmented reality, users not only play with this application but can Learn knowledge about regional musical instruments in Indonesia. Development of the learning system of Multimedia applications regional musical instruments in Indonesia using Augmented Reality technology is able to provide knowledge in learning that is not only in general public but also for children Children who want to add insight into the knowledge of regional culture art, especially local musical instruments in Indonesia